Indeks Risiko Sanitasi Desa Wanasari, Kecamatan Tabanan, Kabupaten Tabanan - Ni Ketut Sri Lestari; Ni Putu Widya Astuti; I Nyoman Purnawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2022)
Environmental Health Risk Assessment (EHRA) is a study to understand the condition of sanitation facilities and behaviors that pose a risk to public health. Wanasari Village is one of the tourist destinations that can have a very complex impact, especially on aspects of environmental health. The purpose of this study was to obtain representative data on the sanitation facilities condition and community behavior in Wanasari Village which are at risk for environmental health. This study uses a stratified random sampling technique with the sample in Wanasari Village as a target study area. The households visited in each Banjar were randomly selected and then interviewed according to the available questionnaires and continued to the next sample until 100 respondents were found for 5 Banjars which were then analyzed. The condition of the facilities and the behavior of the community based on the results of the questionnaire stated that the inadequate facilities were facilities for domestic wastewater and problems with stagnant water. Results of the sanitation analysis risk index with high risk are found in Banjar Wanasari Baleran and moderate risk in Banjar Periyukti with the main problems in domestic wastewater and stagnant water. Banjar Abianlalang, Banjar Wanasari Belodan, and Banjar Wanasari Tengah with the main problems in solid waste, domestic wastewater, and stagnant water are included in the category of less risky areas.